Performance Evaluation of Lighting and Daylighting Retrofits: Results from IEA SHC Task 50. (June 2016) - Dubois, Marie-Claude; Gentile, Niko; Amorim, Claudia Naves David; Osterhaus, Werner; Stoffer, Sophie; Jakobiak, Roman; Geisler-Moroder, David; Matusiak, Barbara; Onarheim, Fredrik Martens; Tetri, Eino
Abstract: This article presents some results from a large monitoring campaign performed in 22 buildings around the world as part of International Energy Agency (IEA) Task 50 "Advanced lighting solutions for retrofitting buildings". This article mainly addresses the work of Subtask D, which aims to demonstrate sound lighting retrofit solutions in a selection of representative, typical Case Studies. In order to evaluate the Case Studies, a monitoring protocol was developed to assess the overall lighting performance taking into consideration: 1) Energy use, 2) Retrofit costs, 3) Photometric assessment, and 4) User assessment. The monitoring was carried out from June 2014 to December 2015 in 22 non-residential buildings in ten countries. This article presents results from selected Case Studies, drawing conclusions regarding retrofit solutions as well as reflecting on methodological procedures for the measurements and data collection. Measured data as well as key conclusions from Subtask D will be summarized in an electronic web and portable sourcebook at the end of the IEA Task 50 (December 2015), which will be freely available through the Internet.